Susceptibility of Bifidobacteria of Animal Origin to Selected Antimicrobial Agents. (16th February 2011) - Mayrhofer, Sigrid; Mair, Christiane; Kneifel, Wolfgang; Domig, Konrad J.
Abstract : Strains of the genus Bifidobacterium are frequently used as probiotics, for which the absence of acquired antimicrobial resistance has become an important safety criterion. This clarifies the need for antibiotic susceptibility data for bifidobacteria. Based on a recently published standard for antimicrobial susceptibility testing of bifidobacteria with broth microdilution method, the range of susceptibility to selected antibiotics in 117 animal bifidobacterial strains was examined. Narrow unimodal MIC distributions either situated at the low-end (chloramphenicol, linezolid, and quinupristin/dalfopristin) or high-end (kanamycin, neomycin) concentration range could be detected. In contrast, the MIC distribution of trimethoprim was multimodal. Data derived from this study can be used as a basis for reviewing or verifying present microbiological breakpoints suggested by regulatory agencies to assess the safety of these micro-organisms intended for the use in probiotics.